Collaborative Product Design and Manufacturing Methodologies and Applications - Li, Wei Dong; Ong, Soh Khim; Nee, Andrew Yeh Ching; McMahon, Christopher Alan (Springer Series in Advanced Manufacturing, 2007)
Recently, there have been major innovations and paradigm shifts in product design methodologies and systems. The current R&D trend is the development of collaborative design and manufacturing methodologies and systems. Using a collaborative product development system, designers can participate in global design chains and collaborate with each other and overseas partners to pursue competitive advantages. It also allows designers to work closely with suppliers, manufacturing partners and customers across enterprise firewalls to obtain valuable inputs for their designs. Collaborative Product Design and Manufacturing Methodologies and Applications is an introduction to a wide spectrum of collaborative engineering issues in design and manufacturing. It contains state-of-the-art chapters written by international experts from academia and industry and reflects the most up-to-date R&D work and applications, especially those from the last three to five years. Collaborative Product Design and Manufacturing Methodologies and Applications is an essential reference for academics, upper-level undergraduate and graduate students and practitioners specialising in collaborative design and manufacturing issues, concurrent engineering, Internet-based/intelligent design and manufacturing, CAD/PDM/CAPP/CAM, Internet applications, product lifecycle management, supply chain, etc.